External Determinants of the Stock Price Performance of Tourism, Travel, and Leisure Firms: Evidence from the United States - Hadi, Dlawar Mahdi; Irani, Farid; Gokmenoglu, Korhan K. (Routledge Journals, Taylor & Francis Ltd, 2022)
This study investigates the effects of the industrial production, exchange rate, commercial and industrial loans, and international tourist arrivals on the stock prices of U.S. tourism, travel, and leisure firms by employing robust econometrics methods. Our study extends the literature by providing evidence for the importance of commercial and industrial loans, a widely ignored variable in the literature, for modeling the stock price performance of the tourism-related firms. Our findings indicate a long-run equilibrium relationship among the variables and reveal causal relationships from industrial production, commercial and industrial loans, and international tourist arrivals toward the U.S. tourism, travel, and leisure firms' stock prices. Obtained empirical results are valuable for several parties, such as portfolio managers, investors, and managers of tourism-related companies.
Keywords: Stock prices; tourism firms; industrial production; exchange rate; commercial and industrial loans; tourist arrivals; USA